Social attitudes toward life sentence in relation to minor and juvenile offenders: replication of Edie Green's and Andrew Evelo's studies (2013) - Jaworska, Anetta (2015)
The article points out some of the differences between Polish and American juvenile penal policy. It shows the differences between Polish and American society in terms of attitudes towards the use of life sentences without the possibility of parole (LWOP) for juvenile offenders. Studies also show that in both (Polish and American) societies, the tendency to impose the harshest sentences reflects the perceived purpose of the penalty.